Knowing Communication Strategy for Better Communication - Rona Merita; Sony Eko Adisaputro (Bahasa Indonesia, 2021)
Nowadays, the importance of communication is undeniable. In oral communication, the learners employ speaking skills which requires the mastery of communication strategies in order to solve the communication problems which they found during oral communication and to get across the communicative goals to the interlocutors. Unfortunately, speaking is still considered one of the most difficult skills to be acquired by English language learners. English learners need more practices and also strategies in communication. In addition, communication ability also influenced by some factors such as target language proficiency, learning and communicating contexts, task types, gender differences and learners’ personality. Driven by this condition, this paper is aimed to discuss theoretical framework about communication strategies and its development since firstly proposed by Tarone (1977). This paper is beneficial for English language practitioner and English language learners, ELT researcher as well.